Audit Portal Sistem Informasi Akademik (PORTALSIA) Menggunakan Framework Cobit 5 Domain DSS dan MEA - Galasca, Syafhira Ananda; Asyiqin, Nora; Haritsyah, Al Hafiz; Handoko, M. Rafli (Lembaga Riset Mutiara Akbar, 2024)
Academic information systems are applications designed for the purposes of academic governance systems such as student data, student ratings, KRS systems, transskip values, etc. By conducting periodic monitoring, it is expected to be corrected when there are complaints or inadequate governance. The steps taken in the audit process are: 1. planning, 2. field work, 3. reporting 4. follow-up actions. The research method used is the method of qualitative approach. By using the calculations of each information technology process available in the domain Delivery and Support (DS) and Monitor, Evaluate and Asses (MEA), so that the entire information technology can reach the desired level. After calculating and rounding the index of processes in the Domain of Delivery, Services and Support (DSS) as well as processes on the domain of Monitoring, Evaluation and Assessment (MEA), it can be seen that there is 1 process with capacity level 4 (predictable), and 7 processes with level 3 capacity (established)